2014
DOI: 10.1093/jnci/djt431
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin, Nonaspirin Nonsteroidal Anti-inflammatory Drug, and Acetaminophen Use and Risk of Invasive Epithelial Ovarian Cancer: A Pooled Analysis in the Ovarian Cancer Association Consortium

Abstract: Aspirin use was associated with a reduced risk of ovarian cancer, especially among daily users of low-dose aspirin. These findings suggest that the same aspirin regimen proven to protect against cardiovascular events and several cancers could reduce the risk of ovarian cancer 20% to 34% depending on frequency and dose of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
173
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(194 citation statements)
references
References 58 publications
15
173
2
4
Order By: Relevance
“…The data for ovarian cancer also suggest a possible inverse association between use of NSAIDs and risk of invasive ovarian cancer although the results of case-control and cohort studies are not consistent. A large pooled analysis of case-control data reported a significant inverse association between use of aspirin and risk of ovarian cancer and a similar, but nonsignificant, association for non-aspirin NSAIDs [70]. By contrast, a meta-analysis of six cohort studies found a future science group www.futuremedicine.com borderline significant association for non-aspirin NSAIDs but no association with aspirin, although a nonsignificant inverse association was again seen for case-control studies [71].…”
Section: • • Nsaidsmentioning
confidence: 98%
“…The data for ovarian cancer also suggest a possible inverse association between use of NSAIDs and risk of invasive ovarian cancer although the results of case-control and cohort studies are not consistent. A large pooled analysis of case-control data reported a significant inverse association between use of aspirin and risk of ovarian cancer and a similar, but nonsignificant, association for non-aspirin NSAIDs [70]. By contrast, a meta-analysis of six cohort studies found a future science group www.futuremedicine.com borderline significant association for non-aspirin NSAIDs but no association with aspirin, although a nonsignificant inverse association was again seen for case-control studies [71].…”
Section: • • Nsaidsmentioning
confidence: 98%
“…With respect to talc powder, results from case control and prospective studies have been variable; one study showed a modest increase in the risk of ovarian cancer, but other studies have shown no increase in risk with talc use (50,51). Aspirin use was associated with a reduced risk of developing ovarian cancer, especially among women who took daily, low-dose aspirin, regardless of their age; the same associations were not shown for acetaminophen (56 Finally, data from the Nurse's Health Study show that persistent depression -defined as meeting the definition of depression based on current and past questionnaires -might increase the risk of ovarian cancer compared with women who do not exhibit depressive symptoms (48) [H1]Mechanisms/pathophysiology…”
Section: [H2] Risk Factorsmentioning
confidence: 99%
“…Ovarian cancer has been linked to several events and conditions which are related to inflammation and repair, including incessant ovulation, endometriosis, exposure to talc and asbestos, and in some studies pelvic inflammatory disease. [Reviewed in [2]] In addition, reduced risks found for aspirin use [3] could be related to direct anti-inflammatory actions, while reduced risks related to tubal ligation and hysterectomy could reflect limited exposure to environmental causes of inflammation. [2] Understanding the role of inflammation in ovarian cancer etiology is complicated by growing recognition that there are least two main types of these tumors, which differ clinically and biologically.…”
Section: Introductionmentioning
confidence: 99%